The Effect of Marketing Capability on Financial Performance with the mediating role of Perceived Sevice Quality and the moderating role of Competitive Intensity. An empirical study on the Banking Sector in Indonesia - Teguh Wibisono Santosa; Hatane Samuel; Devie . (Petra International Journal of Business Studies, 2018)
This research aims to analyze the effects of Marketing Capability towards Financial Performance with Perceived Service Quality as Variable Intervening and Competitive Intensity as Variable Moderating at Banking Company in Indonesia. This research was conducted by distributing questionnaires to 170 respondents who are a customer of Bank. Quantitative analysis with path analysis model method was used for the technical analysis. The results of this research shows that the effect of Marketing Capability on Financial Performance is not significant, but the role of the Perceived Service Quality as an Intervening Variable, is able to strengthen the influence of Marketing Capability on Financial Performance to be a significant influence, and Competitive Intensity as a moderating variable on the relationship of Marketing Capability to Financial Performance does not have a significant effect but has a significant direct effect on Financial Performance.